Effect of LiO Doping on the Surface and Catalytic Properties of NiO Solid - Hala G. El-Shobaky; Gehan A. Fagal; Amina A. Attia; Neven A. Hassan (Adsorption Science & Technology)
The influence of Li 2 O treatment (0.19–0.75 mol%) on the surface and catalytic properties of NiO were investigated using nitrogen adsorption at −196°C and the catalytic decomposition of H 2 O 2 at 30–50°C. Pure and treated solid samples were subjected to thermal treatment at 300°C, 500°C and 700°C, respectively. The results obtained revealed that Li 2 O treatment of NiO solid brought about a measurable decrease (30–63%) in its BET surface area, S BET , and a decrease of 20–44% in its total pore volume, V p , especially for the solid samples calcined at 700°C. The observed decrease in the S BET value of NiO due to treatment with Li 2 O was attributed to transformation of some of the Ni 2+ ions into Ni 3+ ions with a subsequent contraction in the lattice and also to pore widening. The catalytic activities of all the doped catalyst samples investigated showed that their catalytic activity was smaller than that measured for the untreated samples. The catalytic activity, expressed as the reaction rate constant per unit surface area (k), was effectively decreased by the doping process. Although this process increased the number of Ni 3+ ions, it decreased the activity of the treated solids because of the formation of Li + –Ni 3+ ion pairs which could not readily exchange electrons with the reacting substrate (H 2 O 2 ). The formation of such ion pairs may take place at sites associated with the most active Ni 2+ ions. The doping process did not modify the mechanism of the catalytic reaction but decreased the concentration of active sites involved in the catalysis of H 2 O 2 decomposition without changing their energetic nature.